Effect of modified constraint-induced movement therapy along with bimanual massed practice on upper extremity functions in tetraplegics: a pilot study - Chakraverty, Sneha; Walia, Shefali (Bulletin of Faculty of Physical Therapy (Online), 2024)
Background and objective Constraint-induced movement therapy is a widely used rehabilitation program in the stroke population, but its application in spinal cord injury is limited. The objective of the study is to determine the feasibility of modified constraint-induced movement therapy (mCIMT) in incomplete tetraplegia exhibiting upper limb weakness and activities of daily living (ADLs) difficulty. Method This is a quasi-experimental one-group pilot study, consisting of 12 subjects diagnosed with incomplete tetraplegia. They received 2-h sessions of modified constraint-induced movement therapy of the weaker hand along with a 1-h session of bimanual massed practice, 5 days a week for 3 weeks. Apart from this, they were asked to do 3 h of constrained-induced movement therapy daily 5 days a week for 3 weeks at their home as a part of a home exercise program. Box and block test (BBT) and Spinal Cord Independence Measure version III (SCIM-III) were taken as the primary measure, and manual function test (MFT) and capabilities for upper extremity (CUE) were used as secondary measures to access hand functions and ADLs. Subjects were examined during pre-intervention and post-intervention. Results After 3 weeks of intervention, the mean change of the score for the trained hand showed significant changes in the scores of the box and block test ( p = 0.03), manual function test ( p = 0.02), SCIM-III ( p = 0.03), and CUE ( p = 0.02). Conclusion This preliminary study revealed that modified CIMT may be a feasible and effective alternative for hand rehabilitation in incomplete tetraplegia.